Online and computer-assisted career guidance: Are students prepared for it? - Khurumova, Veronika; Pinto, Joana Carneiro (Frontiers in Psychology, 2023)
Career services should be a priority for any higher education institution. These structures should be prepared to support the design, implementation, and evaluation of academic and career plans and decisions, providing services properly aligned with students’ needs, preferences, and characteristics. The present study addressed these questions by analyzing data from an online survey administered to 361 Portuguese higher education students. Results indicate that most students do not seek support in these structures, despite having various needs, particularly in the scope of exploring the world of work, developing goals and implementing career strategies. Most students are open to the use of online and computer-assisted career guidance, although their preference is for in-person interventions. These results allow Career Offices to identify new directions and opportunities to work with students, while demonstrating their value to the academic community and the labor market.